Distribution Of Hand Soap With The Aroma Of Eucalyptus For People Affected By The Covid-19 Pandemic: A Community Service Report - Rasdiana, Felga Zulfia; Novelina, Novelina; Aisman, Aisman; Purnama Dini, Hari; Novizar, Nazir (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2021)
Background: The utilization of liquid hand soap is an alternative to prevent virus transmission inCOVID 19 Pandemic. The production of aromatic hand soap and distribution to the public will be an effortto support the prevention of the spread of the corona virus. Methodology: Aromatic hand soap made fromeucalyptus is produced and distributed to people in Padang City as an alternative product for people tomaintain their personal hygiene. Conclusion: This eucalyptus-flavored handsoap has received a lot ofpositive feedback. This product can assist people in maintaining their personal hygiene. The public does notlike the smell of eucalyptus oil in this hand soap product. The formulation of this product will need to becompleted in the future.